FAKTOR YANG MEMPENGARUHI INDIKASI PENGHINDARAN PAJAK DENGAN CSR SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERTAMBANGAN - Tanriady, Felicia (Media Akuntansi dan Perpajakan Indonesia, 2024)
Tax avoidance is still one of the problem that is prone to occur in Indonesia. Companies will use various methods such as increasing debt structure (thin capitalization) and increasing investment in fixed assets (capital intensity) to increase their profits by minimizing tax payments. These problems have led to low tax revenues received by the state in recent years. Therefore, this study aims to examine the effect of thin capitalization and capital intensity on tax avoidance with corporate social responsibility as a moderating variable. This study uses a sample of mining and energy companies listed on the Indonesian stock exchange for the period 2016 – 2021 using a robust multiple linear regression analysis method. Data were analyzed using Stata 16. The results showed that thin capitalization had no effect on tax avoidance. The capital intensity variable has a negative effect on tax avoidance. The CSR variable strengthens the effect of the thin capitalization variable on tax avoidance. The CSR variable weakens the effect of the capital intensity variable on tax avoidance.